A COMPREHENSIVE REVIEW OF RMU DESIGNS AND THEIR APPLICATIONS IN URBAN AND RURAL ELECTRICAL DISTRIBUTION SYSTEMS - Amin, SM Deen (Academic Journal on Science, Technology, Engineering & Mathematics Education, 2024)
This paper provides a comprehensive review of Ring Main Unit (RMU) technology and its applications in urban and rural electrical distribution systems, analyzing a total of 58 relevant articles. The study identifies three primary RMU configurations: compact, extensible, and modular, each tailored to specific operational requirements. Significant technological advancements, particularly in automation and remote monitoring, have enhanced RMU functionality, allowing for real-time fault detection, isolation, and recovery. These advancements have led to improved operational efficiency and network reliability, with smart grid integration further optimizing electricity distribution and fault management. Case studies from urban environments demonstrate the benefits of compact RMUs in space-constrained settings, while rural applications highlight the robustness of RMUs in managing variable load conditions and harsh environmental factors. The review confirms that RMUs significantly improve key performance metrics, including fault detection accuracy, isolation speed, and recovery times, contributing to reduced outage durations and enhanced network stability. This study underscores the critical role of RMU technology in modern electrical distribution systems, providing evidence of substantial progress and emphasizing the importance of tailored solutions to meet the unique challenges of different environments.